The influence of the magnetic field on the currentvoltage characteristics of cupc nanostructures - Zavgorodniy, A.V.; Aimukhanov, A.K.; Zeinidenov, A.K.; Ayubekova, A.Ye. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The paper presents the results of a study of the role of spin states in the process of charge carrier transfer in copper phthalocyanine (CuPc) nanostructures. It is shown that the film obtained by thermal evaporation has the structure of the α-phase, the CuPc nanowires are in the η-phase. The effect of an external magnetic field on the current-voltage characteristics (IVC) of CuPc nanostructures was studied. It is shown that a decrease in the value of the short-circuit current when an external magnetic field is applied, which is associated with the mechanism of spin polarization in the formation of a bipolaron. It is shown that the effect of “spin blocking” in nanowires is stronger.
Keywords: copper phthalocyanine; nanowires; IVC; charge carrier mobility; magnetic field; spin state